Undescribed morroniside-like secoiridoid diglycosides with α-glucosidase inhibitory activity from Corni Fructus. (March 2020) - Ye, Xian-Sheng; He, Jun; Xu, Jie-Kun; He, Xiao-Li; Xia, Cong-Yuan; Yan, Yu; Lian, Wen-Wen; Zhang, Wei-Ku
Abstract: Corni Fructus, also known as the fruit of Cornus officinalis Sieb. et Zucc., has long been used as a traditional Chinese medicine and is widely consumed as a nutritional food in the form of function drink and wine. Recently, Corni Fructus has attracted considerable interest because of its anti-diabetic effects. A systematic phytochemical investigation of Corni Fructus was performed to find anti-diabetic components, which led to the isolation of 10 unreported iridoid glycosides, cornusdiglycosides A−J (1–8, 9a/9b and 10a/10b ). Their chemical structures were determined through spectroscopic analysis (ultraviolet [UV], infrared [IR], high-resolution electrospray ionisation mass spectroscopy [HRESIMS], one-dimensional [1D] and two-dimensional [2D] nuclear magnetic resonance [NMR]). Such morroniside-type diglycosides were first reported from natural sources, and all isolates were evaluated for α -glucosidase inhibitory activity. The results showed that all compounds (1–10 ) exhibited α -glucosidase (from Saccharomyces cerevisiae ) inhibitory activities with IC50 values ranging from 78.9 ± 4.09 to 162.2 ± 9.17 μ M, whereas acarbose, the positive control, displayed α -glucosidase inhibitory activity with IC50 value of 118.9 ± 7.89 μ M. Graphical abstract: Image 1 Highlights: Ten unreported iridoid glycosides, cornusdiglycoside A−J (1 –8, 9a /9b, 10a /10b ) were identified. All isolates were evaluated for α -glucosidase inhibitory activity. Cornusdiglycoside A−H (1 –8 ) were found to be more potent than that of acarbose.